(untitled) (Agricultural Engineering, 2018)
The process of composting biological waste is a natural process – in which heat is released. Biological wastes generated in typical households in Poland – are mainly kitchen waste (KW) and green waste from home gardens (GGW – if they are owned). From the ecological point of view – the most advantageous method of their management is their utilization in the place of production. The paper presents a proposal for effective management of bio-waste arising by composting – with the simultaneous use of heat for greenhouse heating in autumn. This is to encourage residents to independently compost bio-waste – and increase the level of recycling of waste generated in Poland by 2020. Calculations for greenhouses were made – in accordance with the energy audit methodology. The obtained thermal balance results were compared with the actual temperature prevailing in the greenhouse in autumn. These calculations were the basis for calculating the amount of KW and GGW enabling effective heating of greenhouses in the autumn so that the internal temperature does not drop below 10ºC. It has been calculated that 22 kg of composted bio-waste (KW and GGW) will suffice to heat the greenhouse in October with an area of 18 m2.